Mądrość żartu alternatywą edukacyjną (na przykładzie „Pedagogiki żarto-bliwej” Janusza Korczaka) - Pluta, Andrzej (Studia Edukacyjne, 2019)
The analysis of Janusz Korczak’s actions and beliefs makes him a contemporary Socrates. Socrates is being treated as a classical archetype of Sophomoros, who not only teaches but also plays jokes. In my essay I try to show that in his book entitled Humorous Pedagogy Janusz Korczak presents education and an educator in a way that departs from the one-sidedness of hieratic pedagogy.